Ethnobotanical profile of plant resources utilized by local communities in the Trans-Himalayan Region - Niaz, Nausheen; Abdullah Khoja, Aadil; Azhar Jameel, Muhammad Azhar Jameel; Waheed, Muhammad; Marifatul Haq, Shiekh Marifatul Haq; W. Bussmann, Rainer W. Bussmann (Ethnobotany Research and Applications, 2026)
Background: Plant resources are important sources of livelihood needs, especially for low-income populations living in remote isolated mountain areas, which rely on these plants for food, fuel wood, medicine and building materials. However, traditional knowledge about plant resources is site-specific and passed down orally through generations. Therefore, there is an urgent need to document the traditional ethnobotanical knowledge of these isolated indigenous groups living in remote regions of the Trans-Himalaya. Methods: The study utilized a snowball sampling method to interview participants from diverse professions and age groups, representing local communities residing in the high-altitude mountains of the Trans-Himalaya. This paper presents an ethnobotanical profile of flora and examines how various demographic (gender, age), socioeconomic (education, occupation), ethnic, and cultural (language, livelihood) factors influence knowledge related to plant use. Results: In this study, 49 plant taxa belonging to 41 genera and 29 different families were documented. Rosaceae, Lamiaceae, and Asteraceae were the dominant families used by local communities for multiple uses. The leaves were used most frequently plant part used followed by fruits. Most remedies were prepared as decoctions followed by raw application. The majority of the medicinal plant species were used to treat digestive issues, followed by respiratory issues and dermatological issues. The most important, well-liked, and valuable plant species were Prunus armeniaca, Ficus carica, Rheum australe, Juglans regia, Malus domestica, and Artemisia annua. This shows that plant resources are important across many dimensions of life for people living in distant places, notably for meeting their basic needs for food, housing, livelihoods, and healthcare. Conclusion: By addressing these concerns, we intend to draw attention to the value of traditional plant knowledge in resolving contemporary environmental, social, and economic problems, as well as the necessity of sustainable development to avert catastrophes like the loss of biodiversity and climate change in the future. Keywords: Ethnic groups; Ethnobotanical uses; Social; Economic; High-altitude Mountain; Trans Himalayas; Sustainable development